PJMHS 2022
DOI: 10.53350/pjmhs22165143
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Experience of Breast Cancer Surgeries

Abstract: Aim: To audit the breast cancer surgeries and to establish the age groups and stage at which breast cancer patients present in our institution. Study design: Retrospective study Place and duration of study: Department of Surgery, Jinnah Hospital, Lahore from January 1st 2017 to December 31st 2021. Methodology: Four hundred and seventy-one breast cancer patients were sorted out. The data included the stage of presentation of breast cancer, age at presentation, year of presentation, gender and surgeries performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…They concluded that among the women who breastfed, the longer the duration of breastfeeding, the lower the risk of developing ovarian cancer [23]. Other researchers such as Afzal et al and Abdou-Daoud et al similarly tried to study the relationship between breastfeeding and its role as a protective factor in reducing the risk of cancer in the mother; however, they found no significant role between them [15,18]. Increases the risk 1 (6.25%) [10] Decreases the risk 12 (75%) [11,13,14,16,17,[19][20][21][22][23][24][25] Has no impact 3 (18.75%) [12,15,18] Table 3: Breastfeeding characteristics per study and the final conclusion the study yielded with regards to the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that among the women who breastfed, the longer the duration of breastfeeding, the lower the risk of developing ovarian cancer [23]. Other researchers such as Afzal et al and Abdou-Daoud et al similarly tried to study the relationship between breastfeeding and its role as a protective factor in reducing the risk of cancer in the mother; however, they found no significant role between them [15,18]. Increases the risk 1 (6.25%) [10] Decreases the risk 12 (75%) [11,13,14,16,17,[19][20][21][22][23][24][25] Has no impact 3 (18.75%) [12,15,18] Table 3: Breastfeeding characteristics per study and the final conclusion the study yielded with regards to the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers such as Afzal et al and Abdou-Daoud et al similarly tried to study the relationship between breastfeeding and its role as a protective factor in reducing the risk of cancer in the mother; however, they found no significant role between them [15,18]. Increases the risk 1 (6.25%) [10] Decreases the risk 12 (75%) [11,13,14,16,17,[19][20][21][22][23][24][25] Has no impact 3 (18.75%) [12,15,18] Table 3: Breastfeeding characteristics per study and the final conclusion the study yielded with regards to the hypothesis. Contrary to the previously aforementioned studies, Gustbée et al observed earlier presentation and even more aggressive form of breast cancer type amongst the women who breastfed when compared to those who did not [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This deviation is not surprising considering that there is a higher rate of mastectomies (62-85%) for all types of breast cancers among Pakistani women. 22,33,34 It is plausible that cultural fears of radiation therapy and fear of recurrence may propel women to undergo mastectomies in our setting, despite similar rates of recurrence with both surgical options. As discussed, a lack of access to resources for radiation and surveillance is also a major contributing factor to this decision.…”
mentioning
confidence: 99%